Aromatic aldehyde functionalized polycaprolactone and polystyrene macromonomers: synthesis, characterization and aldehyde-aminooxy click reaction - Sane, Prakash S.; Tawade, Bhausaheb V.; Palaskar, Dnyaneshwar V.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2012)
New bis-aldehyde functionalized initiators, viz, 4,4'-(4,4'-(5-hydroxypentane-2,2-diyl)bis(4,1-phenylene))bis(oxy)dibenza ldehyde (1) and 4,4'-bis(4-(4-(formylphenoxy) phenyl) pentyl 2-bromopropanoate (2) were synthesized starting from commercially available 4,4'-bis(4-hydroxyphenyl) pentanoic acid. These initiators were utilized, respectively, for ring opening polymerization of E-caprolactone and atom transfer radical polymerization of styrene. Well-defined polycaprolactone macromonomers (M-n(GPC): 2600-19400, PDI: 1.37-1.47) and polystyrene macromonomers (M-n(GPC): 2800-28200, PDI: 1.11-1.16) with bis-aldehyde functionality were synthesized. The kinetic study of styrene polymerization showed controlled polymerization behaviour. The presence of aldehyde functionality in macromonomers was confirmed by H-1 NMR spectroscopy. The reactivity of aldehyde functionality was demonstrated by carrying out aldehyde-aminooxy click reaction of polycaprolactone macromonomer with O-(2-azidoethyl) hydroxylamine which proceeded in a quantitative manner without backbone degradation. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde-terminated macromonomers; ATRP; Polycaprolactone; Polystyrene; ROP

Aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups: synthesis and characterization - Bapat, Snehalata P.; Jadhav, Sushilkumar A.; Valsange, Nitin G.; Tawade, Bhausaheb V.; Honkhambe, Pandurang N.; Chavan, Nayaku N.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2017)
A new bisphenol, 1,1-bis-[(4-hydroxyphenyl)-1-(4-phenylsulfonyl) phenyl)] ethane (DPSBP) was synthesized starting from diphenylsulfide and was characterized by spectroscopic methods. DPSBP was polycondensed with isophthalic acid chloride (IPC), terephthalic acid chloride (TPC) and a mixture of IPC and TPC (50: 50 mol%) by phase-transfer catalysed interfacial polymerization method to obtain aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups. A series of copolyesters was also obtained by polycondensation of varying molar proportions of DPSBP and bisphenol-A (BPA) with TPC. (Co) polyesters exhibited inherent viscosities in the range 0.56-1.57 dLg(-1) and number average molecular weights (Mn) were in the range 28,650-80,230 g/mol. Polyesters dissolved readily in common organic solvents such as dichloromethane, chloroform, tetrahydrofuran and aprotic polar solvents such as N-methylpyrrolidone, and N, N-dimethylacetamide. Tough, transparent and flexible films of polyesters could be cast from their chloroform solutions. X-Ray diffraction studies indicated amorphous nature of aromatic polyesters. Polyesters showed T-g values in the range 223-257 degrees C while T-10 values were in the range of 469-484 degrees C indicating their excellent thermal stability.
Keywords: Aromatic polyesters; Bulky pendent group; solubility; thermal stability

Aromatic polycarbonates bearing pendant maleimide groups via functional monomer approach: synthesis and characterization - Nagane, Samadhan S.; Kuhire, Sachin S.; Ichake, Amol B.; Rajamohanan, P. R.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2019)
A new bisphenol containing pendant maleimide group, viz., 4, 4'-(5-maleimidopentane-2, 2-diyl) diphenol (BPA-MA), was synthesized starting from commercially available 4, 4'-bis (4-hydroxyphenyl) pentanoic acid. Aromatic (co)polycarbonates possessing pendant maleimide groups were synthesized by solution polycondensation of BPA-MA or varying mixtures of BPA-MA and bisphenol-A (BPA) with triphosgene in dry dichloromethane in the presence of triethylamine as a base. Inherent viscosities and number average molecular weights of (co)polycarbonates were in the range 0.46-0.66 dL/g and 24,600-36,700, respectively, indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these (co)polycarbonates. (Co)polycarbonates were characterized using FT-IR, H-1 NMR, C-13 NMR spectroscopy, XRD, TGA and DSC analysis. The chemical modification of a representative copolycarbonate containing pendant maleimide groups was carried out quantitatively using thiol-maleimide Michael addition reaction with two thiol compounds, namely, 4-chlorothiophenol and 1-adamantanethiol. Additionally, it was demonstrated that copolycarbonate containing pendant maleimide groups could be used to form insoluble cross-linked gel by reaction with a multifunctional thiol cross-linker, namely, pentaerythritol tetrakis(3-mercaptopropionate).
Keywords: Aromatic polycarbonate; Cross-linking; maleimide group; Thiol-maleimide reaction; Triphosgene

Aromatic polyesters containing pendant azido groups: synthesis, characterization, chemical modification and thermal cross-linking - Nagane, Samadhan S.; Verma, Savita; Tawade, V, Bhausaheb; Sane, Prakash S.; Dhanmane, Sushilkumar A.; Wadgaonkar, Prakash P. (European Polymer Journal, 2019)
A partially bio-based bisphenol containing pendant azido group viz., 4,4'-(5-azidopentane-2,2-diyl) diphenol (AZBPA) was synthesized starting from 4,4'-bis (4-hydroxyphenyl) pentanoic acid. AZBPA was reacted with isophthaloyl chloride (IPC), terephthaloyl chloride (TPC) and a mixture of IPC/TPC (50:50 mol%) by phase transfer-catalyzed interfacial polycondensation route to obtain aromatic polyesters containing pendant azido groups. Copolyesters containing pendant azido groups were also synthesized by polycondensation of different molar proportions of AZBPA and commercially available 4,4'-(1-phenylethane-1,1-diyl) diphenol (BPA-AP) with IPC. Inherent viscosities and number average molecular weights of (co)polyesters were in the range 0.85-1.64 dL/g and 58,900-190,400, respectively, indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these polyesters. X-Ray diffraction analysis showed that (co)polyesters were amorphous in nature. (Co)polyesters were characterized using FT-IR, H-1 NMR spectroscopy, XRD, TGA and DSC analysis. The chemical modification of a representative copolyester containing pendant azido groups was carried out quantitatively using copper-catalyzed azide-alkyne cycloaddition (CuAAC) with two alkynes viz., phenyl acetylene (PA) and ethynyl-4-nitrobenzene (ENB). Additionally, (co)polyesters containing pendant azido groups were thermally cross-linked (170 degrees C/12 h) leading to the formation of network structures based on azide to nitrene decomposition and subsequent reactions on polyester backbone. The selected cross-linked polyesters were characterized by stress-strain measurements. The cross-linked polymers exhibited higher tensile strength and Young's modulus and lower % elongation at break compared to corresponding pristine polyesters containing pendant azido groups.
Keywords: Aromatic polyester; Chemical modification; Click chemistry; Pendant azido group; Thermal cross-linking

Aromatic (co)polycarbonates bearing pendant 2,3-dimethylmaleimido group based upon a new phthalimidine-containing "cardo" bisphenol - Talanikar, Aniket A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2024)
A new ``cardo'' bisphenol viz., 1-(2-(1,1-bis(4-hydroxyphenyl)-3-oxoisoindolin-2-yl)ethyl)-3,4-dimethyl- 1H-pyrrole-2,5-dione (PPH-MA) was synthesized in a two-step reaction sequence starting from phenolphthalein. PPH-MA was utilized as a step-growth monomer for the synthesis of a homo- and fourco-polycarbonates bearing pendant 2,3-dimethylmaleimido groups (PC-MAs) via solution polycondensation of PPH-MA or various mol % compositions of PPH-MA and bisphenol-A, respectively, with triphosgene.H-1 NMR spectroscopy confirmed the chemical structure and composition of PC-MAs. Inherent viscosity and number average molecular weight values of PC-MAs were in the range 0.45-0.64 dL g(-1) and 18,300 - 36,200 g mol(-1), respectively, indicating the formation of polymers of medium to reasonably high molecular weights. Tough, transparent and flexible films of PC-MAs could be cast from chloroform solution. X-ray diffraction studies indicated the amorphous nature of PC-MAs. The 10% weight loss temperature (T-10) values of PC-MAs were in the range 373-443 degrees C indicating their good thermal stability.
Keywords: (co)polycarbonates; 2; 3-dimethylmaleimido; phenolphthalein; phthalimidine ring; ``cardo'' bisphenol

Aromatic (Co)polycarbonates bearing pendant norbornenyl groups: Synthesis, characterization and post-polymerization modification - Talanikar, Aniket A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (High Performance Polymers, 2024)
A homo- and three co-polycarbonates (PC-NBs) bearing pendant norbornenyl groups were synthesized via solution polycondensation of triphosgene with 4, 4'-(bicyclo (2.2.1) hept-5-en-2 yl methylene) bis (2-methoxyphenol) (BPA-NB) or various mol % compositions of BPA-NB and bisphenol-A, respectively. 1H-NMR spectroscopy confirmed the chemical structure and composition of PC-NBs. Inherent viscosity and number-average molecular weight (Mn) values of PC-NBs were in the range 0.44 - 0.64 dL g-1 and 21,800 - 34,100 g mol-1, respectively, indicating the formation of polymers of medium to reasonably high molecular weights. Tough, transparent, and flexible films of PC-NBs could be cast from chloroform solution. X-Ray diffraction studies indicated the amorphous nature of PC-NBs. Glass transition temperature (Tg) values, determined by DSC analysis, of PC-NBs were in the range 154 - 175 degrees C and Tg values increased with the increase in mol % of BPA-NB. The post-polymerization modification of a representative PC-NB was demonstrated using 3,6-diphenyl-1,2,4,5-tetrazine via tetrazine-ene reaction.
Keywords: (co)polycarbonates; norbornenyl groups; post-polymerization modification; tetrazine-ene click reaction; thermoplastics